2008
DOI: 10.1534/genetics.107.085142
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Urinary Albumin in Crosses Between C57BL/6J and A/J Inbred Mice in the Presence and Absence of Apoe

Abstract: We investigated the effect of apolipoprotein E (Apoe) on albuminuria in the males of two independent F 2 intercrosses between C57BL/6J and A/J mice, using wild-type inbred strains in the first cross and B6-Apoe À/À animals in the second cross. In the first cross, we identified three quantitative trait loci (QTL): chromosome (Chr) 2 [LOD 3.5, peak at 70 cM, confidence interval (C.I.) 28-88 cM]; Chr 9 (LOD 2.0, peak 5 cM, C.I. 5-25 cM); and Chr 19 (LOD 1.9, peak 49 cM, C.I. 23-54 cM). The Chr 2 and Chr 19 QTL we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
(35 reference statements)
2
24
0
Order By: Relevance
“…These mice had a minor but statistically significant increase in albuminuria compared with parental strains (22.1 Ϯ 3.7 versus 6.4 Ϯ 2.8, P ϭ 0.02; Figure 2), but this level of albuminuria was well within the range of normal variation for inbred strains (reported range 3 to 142 g albumin/mg creatinine). 19,24,25 We confirmed that Myh9 expression was significantly decreased (by 30%) in Myh9 ϩ/Ϫ mice compared with wild-type littermates (Supplemental Figure 1), which was comparable to the reduction observed in the TgFVB strain. 22 This suggests that reduced Myh9 expression in the TgFVB strain occurs secondary to glomerulosclerosis and is likely not causal in the development of nephropathy.…”
supporting
confidence: 79%
“…These mice had a minor but statistically significant increase in albuminuria compared with parental strains (22.1 Ϯ 3.7 versus 6.4 Ϯ 2.8, P ϭ 0.02; Figure 2), but this level of albuminuria was well within the range of normal variation for inbred strains (reported range 3 to 142 g albumin/mg creatinine). 19,24,25 We confirmed that Myh9 expression was significantly decreased (by 30%) in Myh9 ϩ/Ϫ mice compared with wild-type littermates (Supplemental Figure 1), which was comparable to the reduction observed in the TgFVB strain. 22 This suggests that reduced Myh9 expression in the TgFVB strain occurs secondary to glomerulosclerosis and is likely not causal in the development of nephropathy.…”
supporting
confidence: 79%
“…Future studies could center on tracking and identification of QTL that modify particular cardiac disease-related physiological processes. Previous studies have demonstrated the feasibility of using the genetic homogeneity of inbred mouse strains to isolate and identify physiologically significant QTL (2,6,13,20,21,48,49). In this study, we observed significant functional differences between inbred strains that were evident when subjected to the stresses of ischemia/reperfusion, ␤-blockade, and acute hypoxia.…”
Section: Discussionmentioning
confidence: 59%
“…Even in the absence of engineered or known naturally occurring mutations, different inbred mouse strains can vary drastically in their susceptibility to clinically relevant diseases. Previous reports have taken advantage of this naturally occurring variation in susceptibility to a particular disease to identify quantitative trait loci (QTL) that modify disease pathogenesis (2,6,13,48,49).…”
mentioning
confidence: 99%
“…A portion of the peak on chromosome 13 is orthologous to human region 7p13-15, which contains a locus previously associated with albuminuria (14). The chromosome 19 peak has a 95% CI from 0 to 36 cM, which overlaps the chromosome 19 QTL peak at 24 cM, previously linked with mouse albuminuria (5). The 95% CI of our mouse chromosome 19 peak corresponds to human genomic regions 9q21-q24, 10q11-q26, and 11q12-q13.…”
Section: Discussionmentioning
confidence: 71%